Análise temporal do espectro óptico em redes de Bragg em fibra - Neves Junior, Paulo de Tarso (2008)
This work presents the time analysis of the Bragg wavelength shift in fiber gratings based on the elastodynamics theory and viscoelastic theory. The model is valuable for estimating the maximum tuning speed when traction forces are apllied to the free end of the grating. A comparison between single mode silica optical fiber and polymer optical fiber is performed showing the differences of time response, tuning speed and Bragg wavelength shift when the same longitudinal load is applied on both types of fibers. Also presents the transient and steady state solutions for Assumed Modes method, with potential application on general structures under harmonic longitudinal loads, with mass and stiffness concentrated and variable cross section. Using the combined Assumed Modes and Matrix Transfer method, simulations results were performed on a Bragg grating acousto-optic modulator when a harmonic load is applied. The resulting spectrum and the transient duration were calculated and compared with experimental results related by literature.Furthermore, this work presents a mechanism tuning FBGs, based on a notch type spring principle, which magnifies the displacement of a piezoelectric element stretching a piece of fiber optic. Time response is experimentally acessed for different damping situations of the notch type spring.